The Moderating Role of Perceived Efficacy of COVID-19 Prevention Measures on the Relation Between Perceived Risk and Perceived Mental Health - Cuadrado, Esther; Farhane-Medina, Naima Z; Tabernero, Carmen; Gutiérrez-Domingo, Tamara; Villaécija, Joaquín (Anales de Psicología / Annals of Psychology, 2024)
The pandemic situation caused by COVID-19 led countries to adopt harsh and prolonged (over time) measures that—along with the high number of infections and deaths and continuous negative information—have affected the mental health of individuals. In this study, the impact on mental health of the COVID-19 health crisis in Spain was explored through the perceived efficacy of pandemic containment measures as a moderator of the relationship that COVID-19 perceived risk establishes with stress and depression. A questionnaire composed of scales conceived to measure COVID-19 perceived risk, perceived efficacy of COVID-19 prevention measures, stress, and depression was completed by 478 adults living in Spain (66.9% females, Mage = 36.30, SD = 15.32) between May 16, 2021, and June 6, 2021. The results confirmed the moderating role of perceived efficacy. Perceived efficacy acted as a protective factor for stress and depression by decreasing the negative impact that perceived risk had on both variables related to mental distress. Also, the perception that participants had about the effectiveness of prevention measures appeared to be a relevant protective factor regarding mental health during the pandemic. This study highlights the relevance of psychological interventions and government policies that improve positive risk communication and provide adequate information regarding the effectiveness of health-prevention measures.